2020
DOI: 10.1530/edm-19-0152
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced fulminant type 1 diabetes with C-peptide persistence at first referral

Abstract: Summary A 72-year-old man with no history of diabetes was referred to our department due to hyperglycemia during pembrolizumab treatment for non-small-cell lung carcinoma. His blood glucose level was 209 mg/dL, but he was not in a state of ketosis or ketoacidosis. Serum C-peptide levels persisted at first, but gradually decreased, and 18 days later, he was admitted to our hospital with diabetic ketoacidosis (DKA). The patient was diagnosed with fulminant type 1 diabetes (FT1D) induced by pembrolizumab. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…The HLA phenotype was determined in several case reports whereupon HLA-DR9 (an allele conferring susceptibility to type 1 diabetes) was frequently observed in the patients with type 1 diabetes related to anti-PD-1/PD-L1 therapy (Table 1) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Immune Checkpoint Moleculesmentioning
confidence: 99%
“…The HLA phenotype was determined in several case reports whereupon HLA-DR9 (an allele conferring susceptibility to type 1 diabetes) was frequently observed in the patients with type 1 diabetes related to anti-PD-1/PD-L1 therapy (Table 1) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Most of these events have been described as a case report ( Table 1 ). Cancer patients treated with ICIs present with symptoms collectively described as ICIs-associated pancreatic AEs including abdominal pain, vomiting, dyspepsia, irregular stools, and large daily glucose fluctuations ( 7 , 13 , 32 ). ICIs-associated pancreatic AEs are rare, however they result in poor quality of life and affect safety of patients.…”
Section: Introductionmentioning
confidence: 99%
“…There is some discrepancy in the literature regarding the classification of ICI-induced diabetes as T1DM or fulminant T1DM (FT1DM), and it has been suggested that ICI-induced DM is a distinct pathophysiologic entity with features of both 11 19–22…”
Section: Discussionmentioning
confidence: 99%
“…The time from initiation of ICI to development of ICI-induced DM is variable, ranging from weeks to more than a year after initiation of therapy, with a case series by Galligan et al indicating the majority of patients present within the first month 4 6 11 19 21 22 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation